Landscapes and landforms of the Lesser Antilles - Allen, Casey D. (Springer, 2017)
This book focuses on the highly touristed, but surprisingly under-researched Lesser Antilles region. After offering a brief overview of the region's geologic and tectonic history, as well as its basic climatology, subsequent chapters then discuss each island's (or island set's) geomorphology and geology, and how the settlement history, tourism, and hazards have affected their individual landscapes. Written by regional experts and replete with up-to-date information, stunning color imagery, and beautiful cartography (maps), it is the only comprehensive, scientific evaluation of the Lesser Antilles, and serves as the region's definitive reference resource. Accessible to non-experts and amateur explorers, the book includes in-depth discussions and reference sections for each island/island set. Usable as both a textbook and guidebook, it offers readers a straightforward yet detailed assessment of an interesting and intriguing - but often-overlooked and under-appreciated - locale.
Keywords: Landforms -- Antilles, Lesser.; Geomorphology -- Antilles, Lesser.; Landscapes -- Antilles, Lesser.; Lesser Antilles.; elektronické knihy; electronic books